Sinonasal Mucosal Melanoma Survival Outcomes, Recurrence Patterns, and Prognostic Factors: A Systematic Literature Review and Meta-analysis of Publications after 2000 - Orr, Annie J.; Fenberg, Rachel; Carrau, Ricardo L.; VanKoevering, Kyle (Journal of Neurological Surgery Part B: Skull Base, 2024)
Background Sinonasal mucosal melanoma (SNMM) comprises <1% of all head and neck cancers but has one of the highest 5-year mortalities.Methods A systematic review and analysis using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta- Analyses) guidelines was conducted on SNMM survival, recurrence, and prognostic factors.Results A total of 2,379 abstracts were reviewed resulting in 90 studies describing 3347 SNMM patients. Patients were 49.65% male and 66.5 years old. Surgery plus radiation therapy, followed by surgery only, then radiation only were the most common treatments. Chemotherapy and immunotherapy were used in 418 patients and 101 respectively. The 2-, 3-, and 5-year overall survivals are 55.97, 40.09, and 30.35%, respectively. The 5-year disease-free survival and disease-specific survival are 25.56 and 38.04%. The 5-year local, regional, and distant recurrence-free survivals are 42.35, 81.64, and 44.65%. Mean survival after diagnosis was 26.99 months. Local (n = 650), regional (n = 226), and distant (n = 723) failure presented after 19.36, 6.35, and 12.42 months. Sites of metastasis were lung, liver, bone, brain, skin, kidney, and adrenal glands. Distant metastases, disease in the paranasal sinuses, and higher stage were noted to have worse survival outcomes. Positive margins did not significantly impact overall survival in 11/12 studies.Conclusion Overall survival over 20 years has remained poor with 70% of patients deceased in 5 years. About half of patients will develop distant failure and will thereafter rapidly decline. These data indicate need for advances in treatment of SNMM and new efforts with targeted immunotherapy offer a promising avenue toward improving survival outcomes.
Keywords: sinonasal mucosal melanoma; recurrence; prognosis; PRISMA; survival; immunotherapy